Answer:
y =
![8(-(1)/(2))^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/jaxdig7nl93llawvy58v90p2ddw41y1xw9.png)
Explanation:
Let the equation of the exponential function is,
y = a(b)ˣ
Since the graph of this function passes through two points
and (3, -1)
For the point
,
---------(1)
For second point (3, -1),
-1 = a(b)³ ---------(2)
Divide equation (2) by equation (1),
=
![-(1)/(2)=b^((4-3))](https://img.qammunity.org/2022/formulas/mathematics/high-school/5m9268ixe2oenrav8y0f56fauz05twkbo5.png)
![-(1)/(2)=b](https://img.qammunity.org/2022/formulas/mathematics/high-school/adqogqrn53ttztbknb2ruuzqekdpa3xb03.png)
From equation (2)
-1 =
![a(-(1)/(2))^3](https://img.qammunity.org/2022/formulas/mathematics/high-school/i46an2czded2pth5fvp887s5yatd8yo8wv.png)
-1 =
a = 8
Therefore, equation of the exponential function will be,
y =
![8(-(1)/(2))^x](https://img.qammunity.org/2022/formulas/mathematics/high-school/jaxdig7nl93llawvy58v90p2ddw41y1xw9.png)